Comparing Diffusion Patterns in Affirmative Action Policies for Graduate Education in Brazil. Issue 1 (2nd January 2023) - Venturini, Anna Carolina
Abstract: The paper analyzes how Brazilian public universities and graduate programs used models of admission calls and resolutions from other institutions to formulate affirmative action policies for entry into masters and doctorate courses. The paper compares the diffusion of institutional designs before and after the issuance of Normative Order No. 13/2016 by the Ministry of Education. The research was based on an analysis of admission calls of 2, 763 programs, a survey and semi-structured interviews. The data confirmed that graduate programs looked for models from their universities, other programs within the same field of knowledge, and institutions in the same region.